The answers so far are incomplete.
Let y = sin(2x)
2y^2 + y - 1 = 0
(2y - 1)(y + 1) = 0
so y = 1/2 or y = -1
and since y = sin(2x),
sin(2x) = 1/2 or sin(2x) = -1
If sin(2x) = 1/2
2x = π/6, 5π/6, 13π/6, 17π/6
(you have to go around the circle twice since we will be dividing these values in half
[i.e, if 0 ≤ 2x ≤ 4π , then 0 ≤ x ≤ 2π])
and x = π/12, 5π/12, 13π/12, 17π/12
if sin(2x) = -1
2x = 3π/2 or 7π/2
(again here, we went around the circle twice to find values for 2x, since we will be dividing these in half)
and x = 3π/4, 7π/4
so x = π/12, 5π/12, 3π/4, 13π/12, 17π/12, 7π/4
And the picture is not silly at all, I use them all the time.
However, if you wanted a superscript 2, you could use the character map in windows, or hold down the "Alt" key and type 253 on the number pad, then release the Alt key. Also, sin(x) squared is often denoted sin^2(x).
2006-12-03 09:16:04
·
answer #1
·
answered by Scott R 6
·
3⤊
0⤋
2sin²2x + sin2x - 1 = 0
sin2x = (-1 ± √(1+8))/4
sin2x = (-1 ± √(9))/4
sin2x = (-1 ± 3)/4
sin2x = -1, +1/2
2x = -90°, 30°
x = -45°, 15°
2006-12-03 09:18:11
·
answer #2
·
answered by Helmut 7
·
0⤊
0⤋
Not really a calc problem.
2sin²2x + sin2x - 1 = 0
u = sin2x
2u² + u - 1 = 0
(2u - 1)(u + 1) = 0
u = 1/2 or u = -1
sin2x = 1/2
2x = arcsin 1/2
x = 1/2 arcsin 1/2
sin2x = -1
2x = arcsin -1
x = 1/2 arcsin -1
2006-12-03 09:12:39
·
answer #3
·
answered by Jim Burnell 6
·
1⤊
2⤋
remember, sin(x)/x as x is going to 0 is a million. tan(x)^2 / x => sin(x)^2 / (x * cos(x)^2) => (sin(x)/x) * sin(x) / cos(x)^2 x is going to 0 a million * sin(0) / cos(0)^2 => a million * 0 / a million => 0 Or, shall we use L'hopital's rule, which says that for indeterminate types The decrease of f(x)/g(x) is comparable to the decrease of f'(x)/g'(x) f(x) = tan(x)^2 f'(x) = 2 * tan(x) * sec(x)^2 g(x) = x g'(x) = a million tan(0)^2 / 0 => 0 / 0 this is indeterminate, so we are in a position to apply L'hopital's rule: 2 * tan(x) * sec(x)^2 / a million => 2 * tan(x) * sec(x)^2 x is going to 0 2 * tan(0) * sec(0)^2 => 2 * 0 * a million => 0
2016-10-13 22:40:32
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
2sin²2x + sin2x - 1 = 0
So (2sin2x - 1)(sin2x + 1) = 0
sin2x = ½, -1 (0 ≤ x ≤ 2π → 0 ≤ 2x ≤ 4π)
So 2x = π/6, 5π/6, 13π/6, 17π/6, 3π/2, 7π/2
So x = π/12, 5π/12, 13π/12, 17π/12, 3π/4, 7π/4
= π/12, 5π/12, 3π/4, 13π/12, 17π/12, 7π/4
2006-12-03 09:16:30
·
answer #5
·
answered by Wal C 6
·
0⤊
0⤋
2sin^2(2x)+sin(2x)-1=0
u=sin(2x)
2u^2+u-1=0
(2u-1)(u+1)=0
u=1/2 or u=-1
sin(2x)=1/2 or sin(2x)=-1
we know that sin(pi/6)=sin(5pi/6)=1/2
so x=pi/12 or 5pi/12
we know sin(3pi/2)=-1
so x=3pi/4
in total, x=pi/12,5pi/12, and 3pi/4
2006-12-03 09:11:11
·
answer #6
·
answered by Greg G 5
·
0⤊
3⤋